Particulate Juvenile Articular Cartilage vs Osteochondral Allograft for Patellar Cartilage Defects: A Matched Cohort Analysis. Issue 7 (31st July 2020) - Marom, Niv; Coxe, Francesca; Wang, Dean; Williams, Riley; Ode, Gabriella
Objectives: Management of full-thickness cartilage defects of the patella remains a significant clinical challenge. Osteochondral allograft transplantation (OCA) is a reliable cartilage restoration procedure for large chondral defects of the knee. OCA reports good long-term outcomes for condylar defects but limited literature on outcomes of patellar defects. Since 2007, particulated juvenile articular cartilage (PJAC) has been used as an alternative method of cartilage restoration. PJAC has demonstrated promising early clinical outcomes, however, no studies have directly compared the clinical and patient reported outcomes of PJAC and OCA for management of full thickness chondral defects of the patella. Methods: Prospective data was collected for patients within our institutional cartilage registry who underwent OCA or PJAC using DeNovo NT (Zimmer-Biomet) for management of grade 4 cartilage defects of the patella. OCA patients were matched to PJAC patients by age, sex and BMI. Patient characteristics and minimum 2-year patient reported outcomes (PROMs) (Knee Outcome Survey-Activities of Daily Living (KOS-ADL) score, International Knee Documentation Committee (IKDC) score, Short Form 36 (SF-36) pain rating, and Marx Activity Rating Scale) and self-reported general overall knee condition were reported. Results: There were 28 patients eligible for analysis (14 OCA, 14 PJAC). Demographics of the two groups are outlined in Table 1. The mean age of the entire cohort was 38.4 +/- 11.4 years with a mean BMI of 24.6 +/- 3.1. One patient in each group had bipolar transplantation (patella and trochlea). OCA patients had more previous surgeries (1.4 vs 0.4) (p<0.01) and significantly larger chondral defects (4.6 cm2 vs. 2.5 cm2) (p<0.01) than PJAC patients. Patient reported outcomes are reported in Figure 1. IKDC, KOS-ADL and SF-36-Pain scores improved by 17, 16 and 14 points for OCA compared to 17, 11, and 23 points for PJAC at last follow-up (average 3.5 years) (p>0.05). Both groups met the published MCID for IKDC (17 pts) and KOS-ADL (10 pts) for osteochondral grafts. There was no significant difference between OCA and PJAC for all postoperative PROMs. The reoperation rate for OCA and PJAC was 36% and 50% respectively (p>0.05). There were 4 graft failures in the PJAC group (29%) and 1 failure in the OCA group (6%) (p>0.05). The failed OCA underwent manipulation and lysis of adhesions for post-operative stiffness at 7 months and arthroscopic synovectomy for synovitis at 8 months after OCA. The four failed PJAC patients underwent revision to OCA (at 8 months), chondroplasty of the graft (at 10 and 26 months), and revision to TKA (at 78 months). Reoperations are further described in Table 2.Conclusion: In a matched cohort analysis, both PJAC and OCA demonstrated significant clinical improvement in patient reported outcomes with no significant difference between the two groups at mean 3.5 years. Larger investigational studies are needed to determine optimal indications for use of PJAC versus OCA for management of focal cartilage defects of the patella. Table 1. Patient Characteristics by Group OCA PJAC P value Age (y) 39.1 37.8 0.77 Sex (M:F) 4:10 4:10 1 BMI 24.4 24.8 0.77 Mean # of Prior Surgeries 1.43 0.36 0.0038 Defect Area (c m 2 ) 4.60 2.48 0.0007 Defect Location (Coronal) (n) Central Third-10 Medial Facet- 1 Lateral Facet- 3 Central Third- 7 Medial Facet- 5 Lateral Facet- 2 NA Concomitant Procedures (n) Tibial tubercle transfer- 2 Distal femoral osteotomy- 1 MPFL reconstruction- 1 Tibial tubercle transfer- 5 MPFL reconstruction-1 NA Table 2. Reoperations and Graft Failures for PJAC and OCA PJAC (7 Patients) Time from surgery (mos) OCA (5 patients) Time from Surgery (mos) MUA 2 MUA, lysis of adhesions, fat pad debridement, anterior capsular releaseθ 7 OCA patella, tibial tubercle transfer* 7 I&D and synovectomyθ * 8 Chondroplasty patella (grade III/IV changes of graft); fat pad excision, patella tendon release* 10 HWR tibial tubercle 11 HWR tibial tubercle 16 HWR distal femur 19 HWR tibial tubercle, fat pad excision, patellar tendon release, Chondroplasty medial femoral condyle 23 Tibial tubercle transfer; OCA patella (15 mm graft)** 58 Chrondoplasty patella (grade III/IV changes of graft); HWR tibial tubercle* 26 Lysis of adhesions, medial meniscectomy, HWR tibial tubercle 74 Total knee replacement* 78 *Graft failure θ Same patient ** performed in different location; previous OCA was intact HWR=hardware removal; I&D= irrigation and debridement; MUA=manipulation under anesthesia